Defining Hate: A Content Analysis of State Hate Crime Legislation in the United States of America - Fallik, Seth W. (Victims & offenders, 2024)
Hate crimes have increased in frequency and types of crimes covered, drawing attention to state hate crime statutes. However, hate crime statutes are vague and inconsistent throughout the United States. Variation causes many Americans to no have legal protection against hate crimes and leads to underreporting of hate crimes. Due to this, victims differ in their legal protections, which causes arbitrary outcomes of justice. To evaluate the state of hate crime legislation, this study is a content analysis of all applicable hate crime statutes in the 50 states in the United States, and relevant themes were identified. The general theme of inconsistency was found in conceptualization, protected class and locations, official justice system responses, and victims’ services. Hate crime statutes need improvement which can be accomplished by states mirroring other effective statutes and by legislative action from the federal government.